High energy density physics with intense ion and laser beams - Hoffmann, D. H. H.; Sharkov, B. Yu.; Golubev, A. A.; Zhao, Y.; Fortov, V. E. (21st International Symposium on Heavy Ion Inertial Fusion. Autonomous Organization of Education “Nazarbayev University”, 2016)
We will present the status and perspectives of High Energy Density Physics (HEDP) with intense heavy ion beams as a tool to induce extreme states of matter...
Keywords: high energy; intense ion; laser beams; Research Subject Categories::NATURAL SCIENCES::Physics::Elementary particle physics